Experimental Cannabinoid 2 Receptor-Mediated Immune Modulation in Sepsis - J. Sardinha; M. E. M. Kelly; J. Zhou; C. Lehmann (Mediators of Inflammation)
Sepsis is a complex condition that results from a dysregulated immune system in response to a systemic infection. Current treatments lack effectiveness in reducing the incidence and mortality associated with this disease. The endocannabinoid system offers great promise in managing sepsis pathogenesis due to its unique characteristics. The present study explored the effect of modulating the CB2 receptor pathway in an acute sepsis mouse model. Endotoxemia was induced by intravenous injection of lipopolysaccharide (LPS) in mice and intestinal microcirculation was assessed through intravital microscopy. We found that HU308 (CB2 receptor agonist) reduced the number of adherent leukocytes in submucosal venules but did not restore muscular and mucosal villi FCD in endotoxemic mice. AM630 (CB2 receptor antagonist) maintained the level of adherent leukocytes induced by LPS but further reduced muscular and mucosal villi FCD. URB597 (FAAH inhibitor) and JZL184 (MAGL inhibitor) both reduced the number of adherent leukocytes in submucosal venules but did not restore the mucosal villi FCD. Using various compounds we have shown different mechanisms of activating CB2 receptors to reduce leukocyte endothelial interactions in order to prevent further inflammatory damage during sepsis.